2021
DOI: 10.1590/2317-6431-2021-2552
|View full text |Cite
|
Sign up to set email alerts
|

The use of photobiomodulation for the muscles of head and neck: an integrative review

Abstract: Purpose To carry out an integrative review of the literature on the use of photobiomodulation (PBM) for the head and neck muscles. Research strategy The research took place between June/2019 and March/2021, in the following databases: PubMed, Scopus, Web of Science, LILACS, and SciELO. The MeSH used were Low-Level Light Therapy, Phototherapy, Masseter Muscle, Masticatory Muscles, Tongue, Palate, Mouth, Neck Muscles, and Facial Muscles in English and Portuguese. No limitation was imposed on the year and langua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…In this study, it was observed, through the performance of exercises for the stomatognathic functions and mainly aimed at the rehabilitation of facial mime, which had as objectives the gain of tonus and strength of the oral musculature. 36,37 According to the literature and observed in the reported case, photobiomodulation [38][39][40][41][42] and electrostimulation [43][44][45] associated with orofacial motor exercises 38,41,42,44 promoted positive results in control of saliva flow and ensure greater oromiofacial mobility, accelerating strength gain, maintaining fatigue levels and improving muscle performance. There are still limitations in the literature that do not allow a deeper understanding of the issue, as few articles related speech therapy rehabilitation in patients diagnosed with Tapia´s Syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was observed, through the performance of exercises for the stomatognathic functions and mainly aimed at the rehabilitation of facial mime, which had as objectives the gain of tonus and strength of the oral musculature. 36,37 According to the literature and observed in the reported case, photobiomodulation [38][39][40][41][42] and electrostimulation [43][44][45] associated with orofacial motor exercises 38,41,42,44 promoted positive results in control of saliva flow and ensure greater oromiofacial mobility, accelerating strength gain, maintaining fatigue levels and improving muscle performance. There are still limitations in the literature that do not allow a deeper understanding of the issue, as few articles related speech therapy rehabilitation in patients diagnosed with Tapia´s Syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…A literatura diverge a respeito dos parâmetros dosimétricos que garantam eficácia no uso desta ferramenta, sendo necessárias mais pesquisas para definir os protocolos clínicos de tratamento de disfunção temporomandibular a partir de laserterapia (FERREIRA et al, 2021).…”
Section: Multidisciplinar Vol 4 Capítulo 10unclassified
“…quadros álgicos e de edema, característicos da DTM, devido as suas propriedades antiinflamatórias e analgésicas(FERREIRA et al, 2021). Estudos recentes também abordaram…”
unclassified
“…Photobiomodulation with these wavelengths aims to stimulate biological processes in cells through the absorption of energy by the mitochondria, oxygenate extrinsic laryngeal muscles to promote hyoid bone elevation and promote penetration of light deeper into tissues. The simultaneous use of red and infrared light is believed to provide comprehensive therapeutic benefits, as both wavelengths have complementary effects -red light acts more superficially, while infrared light reaches deeper layers 36,37 . Thus, both superficial and deeper tissues are reached for a more encompassing treatment.…”
Section: • Level IV Mild To Moderate Oropharyngeal Dysphagiamentioning
confidence: 99%